Canine Nervous System Lymphoma Subtypes Display Characteristic Neuroanatomical Patterns. (January 2017) - Sisó, S.; Marco-Salazar, P.; Moore, P. F.; Sturges, B. K.; Vernau, W.; Wisner, E. R.; Bollen, A. W.; Dickinson, P. J.; Higgins, R. J.
Primary and secondary nervous system involvement occurs in 4% and 5%–12%, respectively, of all canine non-Hodgkin lymphomas. The recent new classification of canine malignant lymphomas, based on the human World Health Organization classification, has been endorsed with international acceptance. This histological and immunocytochemical classification provides a unique opportunity to study the histologic anatomic distribution patterns in the central and peripheral nervous system of these defined lymphoma subtypes. In this study, we studied a cohort of 37 dogs with lymphoma, which at necropsy had either primary (n = 1, 2.7%) or secondary (n = 36; 97.3%) neural involvement. These T- (n = 16; 43.2%) or B-cell (n = 21; 56.8%) lymphomas were further classified into 12 lymphoma subtypes, with predominant subtypes including peripheral T-cell lymphoma (PTCL) or diffuse large B-cell lymphoma (DLBCL), respectively. This systematic study identified 6 different anatomically based histologically defined patterns of lymphoma infiltration in the nervous system of dogs. Different and distinct combinations of anatomical patterns correlated with specific lymphoma subtypes. Lymphoma infiltration within the meningeal, perivascular, and periventricular compartments were characteristic of DLBCL, whereas peripheral nerve involvement was a frequent feature of PTCL. Similarly cell counts above 64 cells/μL in cerebrospinal samples correlated best with marked meningeal and periventricular lymphoma infiltration histologically. Prospective studies are needed in order to confirm the hypothesis that these combinations of histological neuroanatomic patterns reflect targeting of receptors specific for the lymphoma subtypes at these various sites.